Net mineral requirements for growth of Saanen goat kids in early life are similar among genders - Mendonça, A. N. [UNESP]; Härter, C. J. [UNESP]; Souza, S. F. [UNESP]; Oliveira, D. [UNESP]; Boaventura Neto, O. [UNESP]; Biagioli, B. [UNESP]; Resende, K. T. [UNESP]; Teixeira, I. A.M.A. [UNESP] (Wiley, 2017)
The current mineral requirements for growing goat kids are based on sheep and cattle studies without differentiating between the stages of development or gender. The aims of this study were to determine the net requirements for growth of Ca, P, Mg, Na and K of Saanen goat kids during the initial stages of growth and to analyse the effect of gender on the net requirements for growth of these macrominerals. Eighteen female, 19 intact male and 10 castrated male Saanen goat kids were studied. The kids were selected applying a completely randomized design and slaughtered when their body weight (BW) reached approximately 5, 10 and 15 kg to determine the mineral requirements for growth at these stages. The net mineral requirements for growth were similar among genders. The goat kids had slightly increased net requirements of Ca, P and Mg for growth with increasing BW from 5 to 15 kg. The net requirements for growth of Ca, P, Mg, Na and K ranged from 9.61 to 9.67 g/kg of BW gain, 7.14 to 7.56 g/kg of BW gain, 0.34 to 0.37 g/kg of BW gain, 1.26 to 1.13 g/kg of BW gain, 1.88 to 1.82 g/kg of BW gain as the animals grew from 5 to 15 kg respectively. In conclusion, when formulating diets for Saanen goat kids in early growth stage mineral levels do not need to adjusted based on gender.
Keywords: body composition; calcium; magnesium; phosphorus; potassium; sodium